Modeling the Multiwavelength Detection of Protoclusters. I. An Excess of Submillimeter Galaxies in Protocluster Cores - Pablo Araya-Araya; Rachel K. Cochrane; Christopher C. Hayward; Robert M. Yates; Laerte Sodré Jr.; Marcelo C. Vicentin; Douglas Rennehan; Roderik Overzier; Marcel van Daalen (The Astrophysical Journal)
Studies of galaxy protoclusters yield insights into galaxy cluster formation complementary to those obtained via “archaeological” studies of present-day galaxy clusters. Submillimeter-selected galaxies (SMGs) are one class of sources used to find high-redshift protoclusters. However, due to the rarity of protoclusters (and thus the large simulation volume required) and the complexity of modeling dust emission from galaxies, the relationship between SMGs and protoclusters has not been adequately addressed in the theoretical literature. In this work, we apply the L-GALAXIES semianalytic model (SAM) to the Millennium N -body simulation. We assign submillimeter flux densities to the model galaxies using a scaling relation from previous work, in which dust radiative transfer was performed on high-resolution galaxy zoom simulations. We find that the fraction of model galaxies that are submillimeter-bright is higher in protocluster cores than in both protocluster “outskirts” and the field; the fractions for the latter two are similar. This excess is not driven by an enhanced starburst frequency. Instead, the primary reason is that overdense environments have a relative overdensity of high-mass halos and thus “oversample” the high-mass end of the star formation main sequence relative to less-dense environments. The fraction of SMGs that are optically bright is dependent on stellar mass and redshift but independent of the environment. The fraction of galaxies for which the majority of star formation is dust-obscured is higher in protocluster cores, primarily due to the dust-obscured fraction being correlated with stellar mass. Our results can be used to guide and interpret multiwavelength studies of galaxy populations in protoclusters.